PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA DITINJAU DARI SELF CONFIDENCE SISWA - Relji Brahim; Nizlel Huda; Evita Anggereini (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
This study applies a problem based learning model that can be a solution for teachers in optimizing students' mathematical problem solving abilities. This study aims to determine the effect of the application of PBL learning models on students' mathematical problem solving abilities, the effect of self-confidence on students' mathematical problem solving abilities, and see the interaction of PBL and self-confidence models on mathematical problem solving abilities. This research is an experimental study using a posttest only control design. The population of this study was all 7th grade students of SMP Negeri 7 Muaro Jambi in the 2021/2022 academic year as many as 248 students and divided into 8 classes. In this study, the sample used was 64 students who were divided into two classes (experimental class I and control class). The sample is determined by the Simple Random Sampling technique. The instrument used in this research is a self-confidence questionnaire and a test of mathematical problem solving abilities. The data obtained were analyzed using a two-way ANOVA test. The results of this study are that the PBL learning model is more effective in influencing mathematical problem solving abilities than conventional learning, and self-covidance with high and medium categories affects mathematical problem solving abilities more than students' self-confidence in low categories.